Effect of epigallocatechin‐3‐gallate on the status of DNA methylation of E‐cadherin promoter region on endometriosis mouse. Issue 10 (24th August 2020) - Guan, Qi‐Hui; Shi, Wen‐Jing; Zhou, Long‐Shu; Tao, Ai‐Lin; Li, Lu
Abstract: Aim: To evaluate whether epigallocatechin‐3‐gallate acts on endometriosis mouse, and changes the status of DNA methylation of E‐cadherin promoter region. Methods: According to our previous research, the tracing nude mouse model of endometriosis was built up and randomly divided into three groups: control group (group A), epigallocatechin‐3‐gallate group (group B) and decitabine group (group C). Normal saline, epigallocatechin‐3‐gallate and decitabine were isometrically intraperitoneally injected into each group once in 2 days. In this period, the growth situations of lesions were monitored by living image system. After 16 days, the lesions were taken out and the distribution of E‐cadherin and its methylated situation of promoter region were analyzed. Results: The region of interest of ectopic lesion increased from 4th to 16th day in group A ( P  < 0.01); in group B and C, the region of interest of ectopic lesion increased in the 0–8th day ( P  < 0.01), and decreased in the 8–16th day ( P  < 0.01). The positive expression rate of E‐cadherin in group C was higher than group B, and group B was higher than group A ( P  < 0.01). The DNA methylation status of E‐cadherin promoter region in group A was higher than group B, and group B was higher than group C ( P  < 0.01). Conclusion: Epigallocatechin‐3‐gallate may inhibit the growth of endometrial lesion, affect the expression of E‐cadherin on the cell membrane and reduce the status of DNA methylation of E‐cadherin promoter region.